Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Morphology on the Monotonic Response of Gravel-Sized Soils through Large-Scale Simple Shear Testing

Abstract: Three gravel-sized materials are tested monotonically using a 305 mm diameter Cyclic Simple Shear (CSS) device and then visually characterized using a Translucent Segregation Table (TST) allowing for an assessment of the impact of particle size and morphology on the shear response of the materials. Three materials are tested to provide a range of particle morphologies and gradations: Pea Gravel, 6AA Limestone, and 5/8"-3/8" Natural Stone. Specimens were prepared in the CSS in loose and dense states. Tests in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Raymond and Diyaljee (1979) also obtained the same test result. Through conducting direct shear tests on mixture of sand (0-2 mm) and gravel (2-6 mm, 2-20 mm), Simoni and Houlsby (2006) and Hubler et al (2014) noticed that material with larger grains showed a higher value of constant volume friction angle. For parameters such as internal friction angle, mobilized internal friction angle, and elastic moduli, similar conclusions were also presented by other researchers (Sitharam and Nimbkar 2000;Ahad and Mirghasemi 2009;Meng et al 2018;Alhani et al 2020).…”
Section: Responsible Editor: Zeynal Abiddin Ergulermentioning
confidence: 99%
“…Raymond and Diyaljee (1979) also obtained the same test result. Through conducting direct shear tests on mixture of sand (0-2 mm) and gravel (2-6 mm, 2-20 mm), Simoni and Houlsby (2006) and Hubler et al (2014) noticed that material with larger grains showed a higher value of constant volume friction angle. For parameters such as internal friction angle, mobilized internal friction angle, and elastic moduli, similar conclusions were also presented by other researchers (Sitharam and Nimbkar 2000;Ahad and Mirghasemi 2009;Meng et al 2018;Alhani et al 2020).…”
Section: Responsible Editor: Zeynal Abiddin Ergulermentioning
confidence: 99%